Literature Review of Practice Evaluation of Good Drug Distribution Methods at Public and Private Sector Pharmaceutical Distribution Facilities in Indonesia: Literature Review of Practice Evaluation of Good Drug Distribution Methods at Public and Private Sector Pharmaceutical Distribution Facilities in Indonesia - As'hari, Yanuar; Wiedyaningsih, Chairun; Yasin, Nanang Munif (Jurnal Surya Medika (JSM), 2024)
To ensure that the quality of pharmaceutical products is maintained throughout the distribution chain, it is necessary to implement Good Distribution Practices at distribution facilities that distribute pharmaceutical products. This literature review explores the evaluation of Good Drug Distribution (GDP) or CDOB guideline practices in pharmaceutical product distribution facilities engaged in the public and private sectors in Indonesia. The literature review method used the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) protocol. Articles were searched using the Google Scholar database and restricted to those related to GDP published from 2018 to 2022. The literature was reviewed using questions to assess studies organized by Population, Exposure, and Outcome (PEO) criteria. Articles obtained were then identified, screened, eligibility, then selected based on inclusion and exclusion criteria resulting in 19 pieces that will be extracted data. Of the 19 articles, the study was conducted in several pharmaceutical distribution facilities such as the Health Office, Puskesmas, Hospitals, Pharmacies, and Pharmaceutical Wholesalers spread across Indonesia. All articles used descriptive methods to show the conformity of implementing Good Distribution Practices guidelines. Some studies still do not use the latest regulation, namely the Food and Drug Administration Regulation Number 6 of 2020 concerning Amendments to BPOM Regulation Number 9 of 2019 concerning Technical Guidelines for Good Distribution Methods. The suggestions that can be made include the need for studies related to the evaluation of Good Distribution Practices of pharmaceutical distribution facilities in the public or government sector and studies on distribution facilities in Eastern Indonesia